Pengaruh Etika Bisnis Islam Dan Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Pelanggan Hotel Syariah Di Bogor - Risma Nur Maulidya; Ahmad Mulyadi Kosim; Abrista Devi (UIN Siber Syekh Nurjati Cirebon, 2019)
This research was aimed to know the influence of Islamic business ethics and the service quality towards customers' satisfication and loyalty, and also to know the influence of satisfication towards customers' loyalty in sharia hotel in Bogor. This research was done in two sharia hotels in Bogor which were Sahira Butik Hotel and Srigunting Inn Hotel. The population of this research was all customers in Sahira Butik Hotel and Srigunting Inn Hotel. The sample of this research was 100 respondents. The method used in this research was quantitative method. For the data analysis, the researcher used Part Least Square (PLS) method by using Samrt PLS 3.0 software. The findings of this research showed that Islamic business ethics had given a significance influence and had positive responses towards customers' satisfication and loyalty. The service quality had given a significance influence and had positive responses towards customers' satisfication and loyalty. The customers' satisfication had given a significance influence and had positive responses towards customers'Â loyalty.